Macroecological patterns of rodent population dynamics shaped by bioclimatic gradients - Soininen, Eeva M.; Magnusson, Magnus; Jepsen, Jane U.; Eide, Nina E.; Yoccoz, Nigel G.; Angerbjörn, Anders; Breisjøberget, Jo Inge; Ecke, Frauke; Ehrich, Dorothee; Framstad, Erik; Henttonen, Heikki; Hörnfeldt, Birger; et al. (Wiley, 2026)
Long-term studies of cyclic rodent populations have contributed fundamentally to the development of population ecology. Pioneering rodent studies have shown macroecological patterns of population dynamics in relation to latitude and have inspired similar studies in several other taxa. Nevertheless, such studies have not been able to disentangle the role of different environmental variables in shaping the macroecological patterns. We collected rodent time-series from 26 locations spanning 10 latitudinal degrees in the tundra biome of Fennoscandia and assessed how population dynamics characteristics of the most prevalent species varied with latitude and environmental variables. While we found no relationship between latitude and population cycle peak interval, other characteristics of population dynamics showed latitudinal patterns. The environmental predictor variables provided insight into causes of these patterns, as 1) increased proportion of optimal habitat in the landscape led to higher density amplitudes in all species and 2) mid-winter climate variability lowered the amplitude in Norwegian lemmings and grey-sided voles. These results indicate that biome-scale climate and landscape change can be expected to have profound impacts on rodent population cycles and that the macro-ecology of such functionally important tundra ecosystem characteristics is likely to be subjected to transient dynamics.